2018
DOI: 10.3390/ijms19124028
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Acid Sphingomyelinase Activity Is Associated with Biomarkers and Phenotypes of Alcohol Use and Dependence in Patients and Healthy Controls

Abstract: By catalyzing the hydrolysis of sphingomyelin into ceramide, acid sphingomyelinase (ASM) changes the local composition of the plasma membrane with effects on receptor-mediated signaling. Altered enzyme activities have been noted in common human diseases, including alcohol dependence. However, the underlying mechanisms remain largely unresolved. Blood samples were collected from early-abstinent alcohol-dependent in-patients (n[♂] = 113, n[♀] = 87) and matched healthy controls (n[♂] = 133, n[♀] = 107), and analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 72 publications
3
28
0
Order By: Relevance
“…A role for sex hormone signaling has been discussed in the development of both alcohol dependence (Lenz et al., ) and handedness (Medland et al., ), which might be a possible link between the 2 conditions. Sexual dimorphisms in alcohol dependence have been repeatedly shown in previous investigations (King et al., ; Lenz et al., ; Mosher Ruiz et al., ; Mühle et al., ; Weinland et al., ), and the present data highlight the importance of sex‐specific analyses in epidemiological and neurobiological studies on alcohol dependence.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…A role for sex hormone signaling has been discussed in the development of both alcohol dependence (Lenz et al., ) and handedness (Medland et al., ), which might be a possible link between the 2 conditions. Sexual dimorphisms in alcohol dependence have been repeatedly shown in previous investigations (King et al., ; Lenz et al., ; Mosher Ruiz et al., ; Mühle et al., ; Weinland et al., ), and the present data highlight the importance of sex‐specific analyses in epidemiological and neurobiological studies on alcohol dependence.…”
Section: Discussionsupporting
confidence: 84%
“…From 2013 to 2014, we recruited 200 alcohol‐dependent patients and 240 healthy control subjects (see Table for cohort characteristics). The following articles including data from the NOAH study have been already published: Lenz and colleagues (), Weinland and colleagues (), Braun and colleagues (), Gegenhuber and colleagues (), Weinland and colleagues (), Mühle and colleagues (, ).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of ASH, ASMase activity and ASMase mRNA levels have been shown to be upregulated in liver biopsies from patients with acute alcoholic hepatitis [51,[82][83][84]. In line with these observations, ASMase activity has been recently linked to biomarkers and alcohol use and abuse phenotypes in patients and healthy controls [85]. On the other hand, the expression and activity of ASMase have been shown to be increased in liver and serum samples from patients with NASH [86,87].…”
Section: Alcoholic and Non-alcoholic Steatohepatitismentioning
confidence: 72%
“…This Special Issue also includes the study by Mühle and colleagues [11], which investigated another type of peripheral biomarkers in alcohol-dependent patients: the acid sphingomyelinase, an enzyme that breaks sphingomyelin into ceramide and thereby changes the composition of plasma membranes. As hypothesized, the authors found clinically relevant changes in the enzyme levels in patients, which also correlated with several other biochemical markers of dependence and health.…”
Section: Biomarkersmentioning
confidence: 99%